ILLOCUTIONARY ACTS PERFORMED IN ATC’S (AIR TRAFFIC CONTROL) UTTERANCES TO PILOT IN FLIGHT SIMULATOR X - SUTRISNO, RIZQY SEPTYANTO TRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: speech act, illocutionary act, syntactic realization, ATC controller Communication between ATC (Air Traffic Control) controller and pilot is a kind of two-way interaction in which messages are produced very attentively because many of the utterances between the ATC controller and the pilot are worth attending for safety reasons. This study focuses on the utterances which are delivered by the ATC controller to the pilot. There are two the objectives of the study; (1) to find out types of illocutionary act found in ATC controller utterances to pilot during the flight, (2) to investigate the syntactic realization of the illocutionary acts. This research applies qualitative approach in relation to the use of clear and systematic description about the language phenomena. Document analysis is the design of this study. The data are transcribed dialogues in Flight Simulator X between the ATC controller and the pilot. The result of the study shows that three types of illocutionary acts (expositives, behabitives, and exercitives) are applied for different purposes. Of the three types of illocutionary acts, it is found that the ATC controller realizes different illocutionary acts using declarative sentences and imperative sentences for some different purposes rather than other types of illocutionary acts. In this case, the ATC controller tends to use direct speech act to show the actions to the pilot. To get more comprehensive study of illocutionary acts, the next researchers are suggested to investigate other elements of speech act since this study focused on illocutionary acts of very formal and strict fixed instructions. The next researchers are also suggested to conduct a study on illocutionary act focusing on other communication context such as speech or religious speech to make illocutionary act study more comprehensive.